There's a trick to proving this result which you would certainly be forgiven for not spotting!
Consider the quantity $\exp(\mu X) \exp(\mu Y)$ which appears on the right hand side. Now differentiate this with respect to $\mu$. Say what!? Yeah, bear with me, just try it:
$$\frac{d}{d \mu} \exp(\mu X) \exp(\mu Y) = X\exp(\mu X) \exp(\mu Y) + \exp(\mu X) Y \exp(\mu Y)$$
This result is hopefully intuitive --- when dealing with matrices, the product rule still works just fine, but we need to be careful with the ordering of things, since matrices don't commute. Now we want to move that $Y$ in the middle of the second term out to the front, since this will allow us to group the $X$ and $Y$ together into $(X + Y)$, which is getting closer to what we want. To do this, we use the commutation relation $[X,Y] = \lambda$, which implies (as you should check) that $[\mu X, Y] = \mu \lambda$.
Of course, what we want to switch is not $\mu X$ with $Y$, but rather $\exp(\mu X)$ with $Y$. Let me just assert, for now, that the commutation relation we need is
$$ [\exp(\mu X), Y] = \mu\lambda \exp(\mu X) $$
Hence the RHS of my first equation becomes
$$X\exp(\mu X) \exp(\mu Y) + Y \exp(\mu X) \exp(\mu Y) + [\exp(\mu X), Y]\exp(\mu Y) $$
$$= (X + Y + \mu\lambda)\exp(\mu X) \exp(\mu Y) $$
What we have here is a differential equation, which doesn't look all that pleasant... But if I just substitute $\exp(\mu X) \exp(\mu Y)$ by, say, $F$, the structure of the equation becomes clearer:
$$ \frac{d F}{d \mu} = (X + Y + \mu \lambda) F $$
Admittedly, $F$ is a matrix here, but despite that, this sort of differential equation should be familiar to you --- it's a first-order linear ODE! Let's write it as
$$ \frac{d F}{d \mu} + p F = 0 $$
where $p$ is defined appropriately. Now the standard method is to multiply through by an integrating factor
$$\exp\left( \int^\mu p \, d \mu \right) $$
such that the differential equation becomes
$$ \frac{d}{d \mu} \left( F\exp\left( \int^\mu p \, d \mu \right) \right) = 0 $$
which is easily solved:
$$ F\exp\left( \int^\mu p \, d \mu \right) = c = \mathrm{constant\ of\ integration} $$
Actually computing the integral inside the exponential, and putting everything back in terms of $X$ and $Y$, gives us a result which looks very similar to the one we're after (note that I've pulled the exponential over onto the right hand side using the result $\exp(A) \exp(-A) = 1$, where $1$ here is interpreted as the identity matrix or the number $1$ as appropriate):
$$ \exp( \mu X) \exp( \mu Y) = c\exp\left(-\int^\mu p \, d\mu\right) = c \exp\left( \int^\mu (X + Y + \lambda \mu) \, d \mu \right) $$
$$ = c \exp( \mu X + \mu Y + \lambda \mu^2 / 2)$$
All that is left to do now is fix the integration constant, which is clearly seen to be $1$ just by setting $\mu = 0$, and take the term in $\mu^2$ over to the other side. It's legitimate to split the RHS into
$$\exp(\mu X + \mu Y) \exp( \lambda \mu^2 /2)$$
since $\lambda$, $\mu$ and $2$ are just numbers, and commute with everything. Note, however, that the essence of this result is that this same, seemingly standard splitting apart of an exponential doesn't work for matrices! And so we're done. Actually I've cheated a little here because I never proved the result $ [\exp(\mu X), Y] = \mu\lambda \exp(\mu X) $. Let me just give you a hint: first prove that
$$[A^n, B] = [A, B]nA^{n-1}$$
for $[A, B] = x$, a number, and use the Taylor expansion of the exponential function.